Prospective Comparison of Intraductal Ultrasonography-Guided Transpapillary Biopsy and Conventional Biopsy on Fluoroscopy in Suspected Malignant Biliary Strictures - Hyun Su Kim; Jong Ho Moon; Yun Nah Lee; Hyun Jong Choi; Hyun Woo Lee; Hee Kyung Kim; Tae Hoon Lee; Moon Han Choi; Sang-Woo Cha; Young Deok Cho; Sang-Heum Park (Gut and Liver, 2018)
Background/AimsIn suspected malignant biliary strictures (MBSs), the diagnostic yield of endoscopic retrograde cholangiopancreatography (ERCP)-based tissue sampling is limited. Transpapillary forceps biopsy (TPB) under intraductal ultrasonography (IDUS) guidance is expected to improve the diagnostic accuracy in patients with indeterminate biliary strictures. We evaluated the usefulness of IDUS-guided TPB in patients with suspected MBS.Methods : Consecutive patients with suspected MBS were prospectively enrolled in the study. ERCP with IDUS was performed in all patients. Both conventional TPB and IDUS-guided TPB on fluoroscopy were performed in each patient. The primary outcome was the diagnostic accuracy of conventional TPB and IDUS-guided TPB.Results : The technical success rate of IDUS-guided TPB was 97.0% (65/67 patients). Of these 65 patients, the final diagnosis was malignancy in 61 patients (93.8%). On IDUS, the most common finding of IDUS was an intraductal infiltrating lesion in 29 patients (47.5%). The overall diagnostic accuracy was significantly higher using IDUS-guided TPB than that using conventional TPB (90.8% vs 76.9%, p=0.027). According to the subgroup analysis based on the tumor morphology, IDUS-guided TPB had a significantly higher cancer detection rate than conventional TPB for intraductal infiltrating lesions (89.6% vs 65.5%, p=0.028).Conclusion : sIDUS-guided TPB appears to improve the accuracy of histological diagnosis in patients with MBS.